Arduino OOP. (Manning Publications, 2022)
Do you want to write Arduino code that you can easily read, modify, and share with other Arduino developers? Do you already know OOP (object oriented programming), and you want to know how to apply it to Arduino? From what I've seen, OOP is not frequently used with Arduino (in libraries, yes, but by most users, no). I noticed this when I got started using Arduino and created a few projects. My initial background was in software engineering, not electronics engineering, so I had a good foundation with OOP applied to desktop software or web development. When coming to Arduino, my thought was why not use OOP on Arduino (because it's possible!). Not many people do it, but it made my programs much more scalable and easy to read--and it worked great. Now, when I write Arduino programs, I almost always use OOP. Seeing that there is a lack of structured resources on the internet to learn how to write OOP code for Arduino, I decided to create this course. I have packaged several years of my experience into this course so you can learn the most important stuff, starting directly with the best practices, and all that in just a few hours. At the end of this course, you will be able to write clean Arduino code with OOP, rewrite your own projects using OOP, and create a clean and super easy-to-use OOP Arduino library.